2018
DOI: 10.3390/toxins10100403
|View full text |Cite
|
Sign up to set email alerts
|

Association of Uremic Toxins and Inflammatory Markers with Physical Performance in Dialysis Patients

Abstract: Association of higher serum levels of uremic toxins and inflammatory markers with poorer physical performance is understudied. We measured the six-minute walk test (6MWT), 10 repetition sit-to-stand test (STS-10), handgrip strength (HGS), and Human Activity Profile (HAP) questionnaire score in 90 prevalent hemodialysis patents, with low comorbidity to reduce the potential confounding of concomitant disease. Midweek pre-dialysis serum levels of asymmetric dimethyl-arginine (ADMA), β2-microglobulin (B2M), high-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 54 publications
1
12
1
2
Order By: Relevance
“…After kidney transplantation, the elimination of toxins is more efficient and as a result the physical capacity of patients is improved [28]. The deleterious action of uremic toxins can be explained by the release of proinflammatory cytokines, which results in a low-grade chronic inflammatory state [29], and the appearance of muscle mitochondrial dysfunction [30]. Of note, total ambulatory EE in our study was fairly close to that of clinical guidelines (30e35 kcal/kg BW/d) [31].…”
Section: Discussionsupporting
confidence: 73%
“…After kidney transplantation, the elimination of toxins is more efficient and as a result the physical capacity of patients is improved [28]. The deleterious action of uremic toxins can be explained by the release of proinflammatory cytokines, which results in a low-grade chronic inflammatory state [29], and the appearance of muscle mitochondrial dysfunction [30]. Of note, total ambulatory EE in our study was fairly close to that of clinical guidelines (30e35 kcal/kg BW/d) [31].…”
Section: Discussionsupporting
confidence: 73%
“…A study conducted in a Japanese dialysis population found a positive correlation between walking test performance and transferrin saturation only, even in a sample of older individuals with lower mean hemoglobin and higher serum phosphorus 17 . In a Slovenian study, it was found that the worst performance in the walking test was associated with higher serum levels of ultrasensitive CRP (variable in ammation cellular), a variable not measured in the present study and perhaps explaining the difference in performance between hemodialysis patients -degree of subclinical in ammation presented and not measured in clinical practice 18 .…”
Section: Discussioncontrasting
confidence: 63%
“…Indoxyl sulfate contributes to renal disease progression, vascular disease, and adverse effects on bones and the central nervous system 23 . No consistent association of various uremic toxin levels, including indoxyl sulfate, with physical performance have been reported, but inflammation is one of the pathways contributing to physical impediment in hemodialysis patients 24 . Considering that higher central or peripheral level of proinflammatory cytokines reduce central BDNF expression and thus impact on neurogenesis and neurotransmitter release, 12 we presume that increased indoxyl sulfate concentrations due to declining kidney function along with longer hemodialysis vintage would be accompanied by proinflammatory responses, which would negatively affect the production of BDNF in skeletal muscles and megakaryocytes, indirectly resulting in impaired physical performances.…”
Section: Discussionmentioning
confidence: 99%